Climate change scenarios and runoff response in the Mulde catchment (Southern Elbe, Germany) - Menzel, L; Bürger, G (Journal of hydrology (Amsterdam), 2002)
The impact of a climate change scenario on regional climate conditions and runoff characteristics has been investigated for the Mulde catchment, a meso-scale sub-basin of the Elbe in Germany. First, the semi-distributed, conceptual model HBV-D has been successfully applied to simulate discharge for present climate conditions. Further, the expanded downscaling method (EDS) was calibrated and applied to observed global circulation fields in order to produce local climate input data for HBV-D. Finally, the coupled atmosphere-ocean model ECHAM4/OPYC3, driven by a climate change scenario, provided simulated global circulation patterns for application with EDS. The regionalised scenario conditions then served as input to HBV-D in order to investigate the impact of global climate change on regional hydrology. The results indicate that an obvious increase in temperature is accompanied by a clear tendency to reduced precipitation over the investigated area for the next 100 years. These conditions lead to a decrease in simulated mean discharges of the Mulde. The study is considered to be a contribution for regional impact studies on global climate change. At the same time, it demonstrates existing shortcomings and limitations of current climate impact research.